Estimation of genetic parameters and response to selection in the irrigated rice populations CNA-IRAT 4PR and CNA-IRAT 4ME - Hideo Nakano Rangel, Paulo; Jose Pfeilsticker Zimmermann, Francisco; Carvalho Ferreira Neves, Péricles (Pesquisa Agropecuaria Brasileira, 1998)
Two groups of irrigated rice (Oryza sativa L.) material with 164 early maturing and 164 medium maturing each were tested, independently, in Goianira (GO) and Formoso do Araguaia (TO), Brazil, using two triple square lattices 10 x 10 and 8 x 8. In each group, 162 lines were S0:2 (families originated from S0 plants self-fertilized twice), drawn from the populations CNA-IRAT 4PR/1/1 and CNA-IRAT 4ME/1/1. The objective was to evaluate the potential of these populations for rice improvement through estimates of genetic parameters and their response to selection. The estimates of genetic coefficient of variation and heritability for yield indicate adequate genetic variability for future genetic gain. Selection based on the classical index was superior to direct selection, increased resistance to panicle blast and to brown spot in selected early maturing and medium maturing populations when compared to the original populations. The data showed that one cycle of selection was eficient in improving the grain yield on the evaluated populations and that they have genetic potential to be used in a recurrent selection program.